(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The mining and metallurgical industries involve labor-intensive processes that expose workers to various occupational hazards, including heavy machinery, high temperatures, sharp objects, and exposure to hazardous chemicals. In such environments, the development of specialized footwear is crucial not only for enhancing worker safety but also for improving productivity and comfort during long working hours. This research focuses on the design and development of advanced protective footwear specifically tailored to meet the demands of employees working in mining and metallurgical plants. The study explores the ergonomic, thermal, and structural requirements of footwear suitable for such extreme conditions. Materials such as heat-resistant leather, reinforced toe caps, puncture-resistant soles, and anti-slip outsoles are critically examined for their functional roles in ensuring durability and protection. Additionally, modern technological integrations, such as smart sensors for pressure and temperature monitoring, are considered to further elevate the utility of the footwear.